Isolation of Escherichia coli and Salmonella spp. from free-ranging wild animals - Iovine, Renata de Oliveira; Dejuste, Catia; Miranda, Flavia; Filoni, Claudia [UNESP]; Bueno, Marina Galvao; Carvalho, Vania Maria de (Soc Brasileira Microbiologia, 2015)
Increasing interactions between humans, domestic animals and wildlife may result in inter-species transmission of infectious agents. To evaluate the presence of pathogenic E. coli and Salmonella spp. and to test the antimicrobial susceptibility of isolates, rectal swabs from 36 different free-ranging wild mammals were taken from two distinct natural sites in Brazil: Cantareira State Park (CSP, state of Sao Paulo) and Santa Isabel do Rio Negro Region (SIRNR, state of Amazonas). The swabs were randomly collected and processed for bacterial isolation, identification, characterization and antimicrobial resistance. Eighteen E. coli strains from CSP and 20 from SIRNR were recovered from 14 and 22 individuals, respectively. Strains from animals captured in CSP, the site with the greatest anthropization, exhibited a higher range and percentage of virulence genes, including an eae+/bfpA+ strain. Antimicrobial resistance was verified in strains originating from both sites; however, in strains from SIRNR, aminopenicillins were almost the exclusive antimicrobial class to which strains exhibited resistance, whereas in CSP there were strains resistant to cephalosporins, sulfonamide, aminoglycoside, tetracycline and fluoroquinolone, in addition to strains exhibiting multidrug resistance. Two strains of Salmonella enterica that are known to be associated with reptiles, serotypes Belem and 60:r:e,n,z15, were recovered only from Amazonian animals and showed susceptibility to all classes of antimicrobials that were tested. Although the potential impact of these pathogens on wildlife remains unknown, bacteria isolated from free-ranging wild animals may provide relevant information about environmental health and should therefore be more deeply studied.
Keywords: E. coli; Salmonella; wild mammals; One Health; Brazil